PENGARUH SERTIFIKASI GURU TERHADAP PROFESIONALISME DAN KINERJA GURU PADA JENJANG PENDIDIKAN DASAR - Alfian Husin; Ramdhan Witarsa; Nurmalina Nurmalina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2023)
The unclear implementation of teacher certification evaluation is one of the issues behind this research. Teacher certification should be evaluated at least annually by school principals. This research aims to measure the effect of teacher certification on teacher professionalism and performance at the primary education level. The method used in this research is the quasi-experimental method. This method has nine stages, namely: literature review, identifying and limiting the research problem, developing research hypotheses, creating a research design, conducting pretests, conducting experiments, conducting post-tests, processing and analysing data, and drawing conclusions. The research sample totalled 38 teachers, consisting of 19 teachers in the experimental group and 19 teachers in the control group. The data collection techniques used were professional competence tests and teacher performance. The results show that teacher certification has a significant effect on teacher professionalism and performance at the primary education level in group A/experiment. Teachers should be encouraged to obtain teaching certificates to improve their professionalism and performance. Research on the effect of teacher certification can be continued by future researchers in terms of measuring teachers' pedagogical competence. How much influence does teacher certification have on pedagogical competence.